Representaciones discursivas de El caso Banchero - Dávila Díaz, Lucina Dionela (2020)
The purpose of this article is to show the different discursive representations of The Banchero case: historic, journalistic and fictional (literature and cinema). Luis Banchero Rossi's historic recognition is significant, since he is a businessman, tenacious and persevering, a great example to follow. Concerning the historic speech, the assessment of his personality as a fishing businessman within history and his relevance will be observed for Peru. The journalistic speech is observed in the investigation of the murder of the character and the later treatment of the process (debate) by the written media (magazines and newspapers) and television. The fictional speech is observed from the literary works that are based on Luis Banchero's life and death or that, by the fishing context that is developed in the plot, where he is mentioned. This is also observed in the analysis of the film A business tycoon's death, directed by Francisco Lombardi and projected at the movie theaters in 1981.